Development and Design of Flexible Sensors Used in Pressure-Monitoring Sports Pants for Human Knee Joints - Yu, Miao; Jin, Jiaqin; Wang, Xia; Yu, Xu; Zhan, Dingjia; Gao, Jia (IEEE sensors journal, 2021)
Flexible pressure sensors are being used widely in sports and human-health monitoring. The knee joint is one of the organs with the highest injury rate while running. By optimizing the structural design of sports pants, the lower limbs can be compressed appropriately to protect the knee joint and improve exercise efficiency. The point of innovation lies in the removable flexible pressure sensors implanted in these leggings developed to monitor the three-dimensional force on the knee in real time. Combined with data analysis, this can provide information to wearers while exercising and to the middle-aged and elderly to prevent knee-strain problems. The experimental results showed that the pressure values of the left and right knee joints measured using the flexible pressure sensors on the leggings in real time and those obtained using the AMI3037-5s Airbag pressure tester were accompanied by F-values and t-test statistical probability values greater than 0.05. This indicates that there was no significant difference between the two values, reflecting the credibility of the flexible pressure-monitoring data. The oxygen saturation and total hemoglobin content of a subjects' legs after exercising were higher than those before exercising, indicating that the leggings performed well in terms of fatigue relief. The subjects' body surface temperature, when exercising, changed steadily and dropped gradually in the later stage, indicating that the leggings perform well with respect to thermal and moisture comfort. Flexible sensing technology has promising application prospects in wearable smart clothing in future, particularly in the sports and health fields.